Effective factors for increasing university publication and citation rate - Shahbazi-Moghadam, M.; Salehi, H.; Ale Ebrahim, N.; Mohammadjafari, M.; Gholizadeh, H. (Canadian Center of Science and Education, 2015)
Despite the vital role of paper publication and citation in higher education institutions (HEIs), literature on publication exercises is relatively scarce. There are a number of factors which influence the rate of university publications and citations. Accordingly, with a focus on policy perspectives, this paper discusses publication exercises by addressing the factors that can increase or decrease the rate of publication and citation in HEIs. The investigated zones are divided into two macro and micro levels, in which macro level deals with global policy and micro level is related to local and university policies. The effective factors and their relevant criteria are traced in all the aforementioned policies.